2016
DOI: 10.1037/tra0000101
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement desensitization and reprocessing (EMDR) for DSM–5 posttraumatic stress disorder (PTSD) in adults with intellectual disabilities: A case study review.

Abstract: EMDR is a safe and acceptable intervention for people with intellectual disabilities, and there is now sufficient evidence to conduct a randomized control trial to establish its effectiveness for DSM-5 PTSD in this population group. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…There is an established association between exposure to life events and subsequent psychopathology (Hatton & Emerson ; Esbensen & Benson ; Hulbert‐Williams & Hastings ; Jowett et al . ). Little is known about the association between multiple traumatisation and severe psychopathology such as DSM‐5 post‐traumatic stress disorder (PTSD) and symptoms of anxiety and depression in adults with ID.…”
Section: Introductionmentioning
confidence: 97%
“…There is an established association between exposure to life events and subsequent psychopathology (Hatton & Emerson ; Esbensen & Benson ; Hulbert‐Williams & Hastings ; Jowett et al . ). Little is known about the association between multiple traumatisation and severe psychopathology such as DSM‐5 post‐traumatic stress disorder (PTSD) and symptoms of anxiety and depression in adults with ID.…”
Section: Introductionmentioning
confidence: 97%
“…Unfortunately, there has been no trial on the clinical and cost‐effectiveness of either TfCBT or EMDR for PTSD in people with intellectual disability. Nevertheless, there have been numerous published positive case studies on EMDR for psychological trauma in people with intellectual disability (Jowett et al, ). In their case studies review, Jowett et al () concluded that overall EMDR is an acceptable and potentially efficacious treatment for people with intellectual disability and psychological trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there have been numerous published positive case studies on EMDR for psychological trauma in people with intellectual disability (Jowett et al, ). In their case studies review, Jowett et al () concluded that overall EMDR is an acceptable and potentially efficacious treatment for people with intellectual disability and psychological trauma. A range of forms of bilateral stimulation was used across case studies, with visual stimulation being the preferred method and others such as auditory, tactile and tapping being used to meet the needs of different participants.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only a small number of studies have been carried out investigating the use of various therapies for treating PTSD in people with intellectual disability and there is currently limited advice on the most effective treatment options. Previous studies include a small number of case studies describing the effectiveness of EMDR and psychodynamic therapy in reducing trauma‐related symptoms (Jowett et al, ; Mevissen, Didden, & Jongh, ; Mevissen & de Jongh, ). A further pilot study of Tf‐CBT reported a medium effect size in reducing trauma‐related distress for people with intellectual disabilities (Stenfert‐Kroese et al, ).…”
Section: Introductionmentioning
confidence: 99%